Dimensões de inovações organizacionais e sociais no processo de certificação fair trade: o caso da Casa Apis - Ferreira, Johnny Herberthy Martins (2012)
The exclusion of small producers in the global market is characterized as a major obstacle to the development of the underprivileged section of society. As a result, small producers, associated in cooperatives are seeking new markets and promoting the inclusion of products from family agricultural in the international market through fair trade (fair trade). Therefore, the development of social and organizational innovations become part of an alternative to overcome this challenge. Thus, the aim of this study is to analyze the dimensions of social and organizational innovations in the certification process in a fair trade cooperative central bee in northeastern Brazil. The qualitative research was conducted through a case study along with a Central Cooperative Apicultural the Brazilian Semiarid - Home Apis - consisting of eight member cooperatives. The theoretical discourses on organizational innovations, social innovations and fair trade certification. Primary data was collected through semi-structured interviews and diaries entries field. Since the secondary data were collected via documents, articles, dissertations and web sites. Data analysis was performed according to the theoretical framework of this study and the use of the technique of content analysis (BARDIN, 1995) and triangulation of different sources of evidence (YIN, 2005). The results were based on the requirements of FLO (Fairtrade Labelling Organizations International) on fair trade certification process and showed the dimensions of organizational innovation in the areas described by Lam (2004) and the dimensions of social innovation described in the model developed by CRISES (Centre de Recherche sur les innovations sociales) of Canada. The dimensions for the analysis of organizational innovation were the "organizational structure", "the process of learning and knowledge creation" and "organizational change and adaptation." Regarding social innovation, the dimensions analyzed were the social innovations "territorial", the social innovations in "labor relations and employment generation" and social innovations in "conditions of life". The low formalization documentary cooperatives, producers with little knowledge about fair trade, non-compliance with statutory and little financial resources were some of the obstacles and barriers identified in the fair trade certification process. Among some of the issues identified in the analysis of the dimensions of organizational innovation are featured: the organization of the production base, the partnership of various institutions to support and process development for export of honey fair trade. The fair trade honey with a minimum price guaranteed a fair price to beekeepers, the award fair trade and support networks were the most reported in the dimensions of social innovation.